Pengembangan Kapasitas Pegawai untuk Mewujudkan Good Governance pada Kantor Badan Kepegawaian dan Pengembangan Sumber Daya Manusia (BKPSDM) Kota Palembang - Yofitri Heny Wahyuli (MAP Program Pascasarjana Universitas Sjakhyakirti, 2019)
Abstract: Capacity Building of Public Servants to Attain Good Governance (Study at The Office of Personel agency and human resource development (BKPSDM) Kota Palembang). The realization of good governance needs professional and competent public servants. Early step that shall be taken by local government is capacity building of public servants in every public organization in the local. One public organization that is Local Employment Agency of Palembang city. Result of research indicates that capacity building of public servants at Local Employment Agency of Palembang City in general has been quite well. Employee transparency for information openness is not working optimally. Employee responsiveness to administrative service is adequate. Employee equality in delivering service is sufficient. Capacity building of public servants must be supported by enthusiastic leadership which drives employee and collective commitment based on work contract and employee agreement. Employee must be made understood through socialization, internal session or even internal regulation.